2021
DOI: 10.3126/jgmcn.v14i2.40021
|View full text |Cite
|
Sign up to set email alerts
|

A study of height, weight and body mass index in Nepalese

Abstract: Introduction: The height measurement is an important anthropometric measurement which can be directly correlated with health status of an individual. Body weight of an individual refers to total body mass and is also important indicator of health status of people. Body mass index (BMI) is a key index for relating weight to height. It is defined as the body mass divided by the square of the body height, The BMI is an attempt to quantify the amount of body tissue mass  in an individual, and then categorize that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The average BMI of participants in our study was 20.3 ± 3.1 kg/m 2 . A cross-sectional study conducted in 2021 in Nepal showed that the average BMI of the overall population was 20.9 ± 1.8 kg/m 2 [ 16 ]. Likewise, another descriptive cross-sectional study conducted among the medical students of Nepal showed that the average BMI was 20.8 ± 2.4 kg/m 2 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The average BMI of participants in our study was 20.3 ± 3.1 kg/m 2 . A cross-sectional study conducted in 2021 in Nepal showed that the average BMI of the overall population was 20.9 ± 1.8 kg/m 2 [ 16 ]. Likewise, another descriptive cross-sectional study conducted among the medical students of Nepal showed that the average BMI was 20.8 ± 2.4 kg/m 2 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The eye level was determined based on the average height of persons in Nepal. [7]. Figure 1 shows the measurement procedure of the illuminance as suggested by different studies [8,9].…”
Section: Methodsmentioning
confidence: 99%